Electronic communication in ethics committees: experience and challenges. (1st April 2001) - Eiser, Arnold R; Schade, Stanley G; Anderson-Shaw, Lisa; Murphy, Timothy
Abstract : Experience with electronic communication in ethics committees at two hospitals is reviewed and discussed. A listserver of ethics committee members transmitted a synopsis of the ethics consultation shortly after the consultation was initiated. Committee comments were sometimes incorporated into the recommendations. This input proved to be most useful in unusual cases where additional, diverse inputs were informative. Efforts to ensure confidentiality are vital to this approach. They include not naming the patient in the e-mail, requiring a password for access to the listserver, and possibly encryption. How this electronic communication process alters group interactions in ethics committees is a fruitful area for future investigation.